Aktivitas Event Sastra melalui Pameran Manuskrip Minangkabau dan Produk Industri Kreatif oleh SURI - Hanifa, Septiara; Saniro, Roma Kyo Kae (Puitika, 2023)
A descriptive research method with a philological approach is used in this study. Field study methodologies and literature research were used to collect data. The article will explain the illumination of manuscripts through the formulation of the problem, which includes the understanding of SURI, the Relationship between Literary Event Activities and the Purpose of Forming a Creative Industry from SURI, the Exhibition of Manuscripts and Creative Products of the SURI Industry as a Form of Tourism Literary Event Activities, and the meaning behind the illumination of manuscripts contained in SURI products. The goal of this article is to understand and know that the SURI exhibition may be used as a valuable event activity involving tourism, as well as to explain why there are still many manuscripts that have not been researched about the meanings and philosophies in West Sumatra. The findings of this study are theoretical in terms of the research hypotheses proposed, as well as practical in terms of revealing how the literary activities, as well as the philosophy and meaning behind the illumination of Minangkabau manuscripts in West Sumatra.